5 - Aesthetic of Innocence: Experiencing Self-filming by the San of Zimbabwe - Ureke, Oswelled; Mhiripiri, Nhamo A.; Mubayiwa, Mercy Mangwana; Midzi, Ratidzo (Africa Development, 2021)
This article discusses the process and outcome of a participatory video production endeavour in which selected members of the Twai Twai San community in Zimbabwe were taught to operate video cameras and mobile phones for the purpose of documenting their realities. The study was aimed at finding out the nature of audio-visual narratives that the marginalised community would create if empowered to do so. The article pays particular attention to representations of the self by the San community, the underlying power dynamics and socio-technical concerns of the production process. A combination of participatory action research and filmmaking methodology was employed for the study. Data for the study were collected through interviews and focus group discussions with the filmmakers and some members of the community. The article also benefits from the authors’ observations of the film production process, which is critical in the analysis of the completed ethnographic video-films The Golden Story of Makhulela and The San of Twai Twai. The study established that the films made by the San youths projected the ways in which they perceived themselves as a community. As such, the films were some form of self(ie)-representation. This perception of themselves could be the chief reason behind the film techniques employed and narratives chosen by the San youth as well as the aesthetics of the video-films. It was also found in the study that video-film could play a critical role of preserving or archiving Tyua language, which is slowly dying among the San.